Analysis and comparison of the trends in burden of intracerebral hemorrhage in China from 1990 to 2021: results from the 2021 Global Burden of Disease Study - Han, Shuai; Wang, Zirui; Zheng, Qiuyue; Mao, Hua; Gao, Ju (Frontiers in Neurology, 2025)
ObjectivesTo analyze temporal trends in the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of intracerebral hemorrhage (ICH) in China from 1990 to 2021, and to evaluate risk factors and predict future trends.MethodsData were extracted from the 2021 Global Burden of Disease Study. Join-point regression was used to estimate average annual percentage changes (AAPC) in ICH incidence and mortality. Age-period-cohort analysis assessed demographic effects, while the autoregressive integrated moving average (ARIMA) model projected ICH burden from 2020 to 2036.ResultsIn 2021, China reported 3.12 million ICH cases and 913,023 deaths (68.84 per 100,000). From 1990 to 2021, ICH incidence and mortality significantly declined, with AAPCs of −1.90 and −2.42, respectively. Males exhibited higher rates, and key risk factors included low vegetable intake, hypertension, and smoking. Projections suggest further declines in incidence and mortality to 50.37 and 35.01 per 100,000 by 2036.ConclusionsDespite declining trends, ICH remains a significant public health concern in China. Targeted preventive strategies focusing on dietary improvements, hypertension management, and air quality enhancement are essential to mitigate its burden.